MODERN LEGAL HERMENEUTICS AS A MECHANISM OF INTERPRETATION OF PRINCIPLES AND VALUES IN LAW - Trofymenko, Volodymyr; Yurkevych, Olena; Danilyan, Vadim; Pavlenko, Zhanna; Kovalenko , Hanna (Revista Inclusiones, 2020)
The purpose of the article: the reflection of legal hermeneutics as one of the main mechanisms for the interpretation of the principles and values of law. The research methodology is based on a complex combination of general scientific (analysis, synthesis, analogy, etc.), philosophical (hermeneutical) and special legal (regulatory and analytical, comparative legal) methods. The scientific novelty of the work in the disclosure of consists in revealing the significance of legal hermeneutics as one of the main mechanisms for interpreting the principles and values of law, as well as the study of the possibilities of applying legal hermeneutics in reformed legal systems. Conclusions. The need to apply hermeneutical practices in law arose due to the discrepancy between the concepts of «legal act» and «law». Statutory instrument is considered only as a guide on the road to living law. At the same time, while awarding judgement, the judge must understand what the legislator has invested in the content of the law and how to interpret it in a particular case. Thus, it is obvious that the legal hermeneutics expressively demonstrates the essence of law as a pure legal, natural one. Legal hermeneutics acquires a new axiological level, which opens up a new way to the perception of a person, his rights and freedoms by the highest social values. The absence of a legislative monopoly on lawmaking makes it possible to take into account the significance of legal values and principles at all stages of the creation and application of law.